HISTOPATHOLOGICAL EFFECTS OF CADMIUM EXPOSURE ON TESTIS TISSUE OF SWORDTAIL FISH, Xiphophorus helleri (Pisces: Poecilidae) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2015)
Heavy metal contamination of the aquatic environment has drawn increasing attention as it may have devastating effects on the ecological balance of the recipient environment and a diversity of aquatic organisms. Cadmium (Cd) is one of the toxic heavy metals which is widely used in industry and is released into the aquatic system. This present study was done to investigate the histopathological effects of cadmium on testis tissue of swordtail fish (Xiphophorus helleri). Histological studies in testis of swordtails were made to assess tissue damage due to sublethal concentrations (0.1 ppm and 0.5 ppm) of Cd after 5 days of exposure. In this study, it is observed that Cd causes degeneration at seminiferous tubules, openings at spermatogenetic cells and clumping of primary and secondary spermatocytes.
Keywords: cadmium; histopathology; testis; swordtail fish; INDUCED TESTICULAR DAMAGE; HEAVY-METALS; DIPHENYL DISELENIDE; LATES-CALCARIFER; ACCUMULATION; TOXICITY; COPPER